In vitro and in silico analysis of xanthine oxidase inhibitory activity of peanut (Arachis hypogaea L.) shell ethanol extract. Issue 1 (April 2020) - Alvionita, M; Dewi, L C; Subandi,; Suharti,
Abstract: Gout is common inflammatory arthritis caused by the formation of uric acid crystals in a joint. This product is generated by the oxidation reaction of xanthine catalyzed by xanthine oxidase enzyme (XO). Since their influence in gout disease, the discovery of XO inhibitor agents has gained many interests, mainly from natural resources. Some studies showed that bioactive product can replace the common gout medicine, allopurinol, which known to have many negative effects. Thus, this study aimed to determine the inhibitory activity of the bioactive product of peanut shell extract toward xanthine oxidase (XO). Moreover, the inhibitory activity of predicted compounds using in silico analysis was also conducted. There are 4 steps in this work, namely: (1) ethanol extraction of bioactive compounds from peanut shell, (2) phytochemical analysis, (3) in vitro analysis as XO inhibitor and (4) in silico study of predicted bioactive compounds from peanut shell as XO inhibitor. The results had shown that Arachis hypogaea L. epidermis extract contained tannins, polyphenols, flavonoids, alkaloids, and terpenoids, whereas their outer peel extract has the same contents, except tannin. At the same concentration (100 ppm), the inhibition activity of epidermis and peanut shells extract towards XO were equivalent to 12 and 14 ppm of allopurinol, respectively. According to the previous study, the bioactive compounds in the peanut shell were luteolin, 5, 7-dihydroxychromone, and eriodictyol. Our in silico analysis has revealed that each of those compounds has binding affinity higher than allopurinol has.